RESPON TANAMAN JAGUNG PULUT (Zea mays ceratina Kulesh) AKIBAT BERBAGAI DOSIS PUPUK NPK PHONSKA DAN JARAK TANAM ANTAR BARIS - Yohanes Kristono Fowo; Josina Irene Brigetha Hutubessy; Elisebet Ndae (Agrica: Journal of Sustainable Dryland Agriculture, 2022)
Waxi corn, which is included in the cereal plant group, is a food source for meeting the needs of life and has an important role in fulfilling community nutrition. Efforts to increase production that include quantity and quality can be made by applying NPK phonska fertilizer and spacing out planters to minimize the occurrence of competition. The study was to obtain the interaction caused by various doses of NPK phonska dose with different spacings on maize plants and to obtain the optimum dose of NPK phonska and ideal spacing to produce the optimum pulut maize plant. Using a factorial randomized block study design (RAKF)consisting of two treatment factors, each combination was repeated 3 times. Phoska NPK treatment consists of three levels (P1:50; P2:100 and P3:150)kg/ha, While the spacing treatment includes (J1: 50x 40; J2: 60x40 and J3: 70x40) cm. Data is collected non-descriptively. level F test5% to go to treatment. The interaction effect is based on Duncan's 5% test and LSD 5% test for a single treatment difference phonska test on the variable length of cropping cobs and yield hectare with a percentage increase of 15,19% and 28,33% respectively, the single treatment of plant spacing had a significant effect on the variable cob weight cropping weights 33,73%.